Numerical simulation and experimental verification of venturi tube hydraulic cavitation - Zhanshuo Zhang; Sitong Guo; Xueying Ji; Linlin Cao; Zhanshan Ma; Yunsheng Tian; Xiaolong Zhou; Zhijie Huang; Xiaobo Liu (PLoS ONE, 2026)
This study conducted a numerical simulation of hydraulic cavitation characteristics in a Venturi tube using FLUENT software. The Realizable k-ε turbulence model, Mixture multiphase flow model, and Singhal cavitation model were employed to investigate the effects of inlet pressure, outlet cone angle, and throat parameters (diameter and length) on cavitation performance. A critical inlet pressure threshold (~1.5 MPa) exists, beyond which the cavitation growth rate significantly decreases. Increasing the outlet cone angle weakens cavitation intensity due to reduced pressure recovery efficiency. Larger throat diameters enhance cavitation generation, whereas extended throat lengths suppress it by prolonging pressure recovery. Experimental validation demonstrated consistent trends between temperature variations, conductivity measurements, and simulation results, confirming the validity of the numerical methodology. These findings provide theoretical guidance for optimizing Venturi tube structures in industrial applications such as wastewater treatment and chemical reactors. The systematic analysis of parameter interactions offers practical insights for cavitation control and device performance enhancement.